On momentum crashes : A triple-screened momentum strategy - Ursin, Simo (My University, 2021)
Momentum anomaly, an idea that past returns can predict near-future returns, remains one of the most persistent and puzzling features of the financial markets. Using a strategy that goes long in past winner stocks and short in past losers is widely confirmed to generate abnormal risk-adjusted returns across time, different markets and asset classes. Literature has documented that this effect exists both when implemented based on relative performance of stocks in a stock universe (cross-sectional momentum) as well as based on a stock’s absolute performance alone (time series momentum), though the academics are more inconclusive of the latter. Despite the anomalous performance, momentum strategies may be subject to severe losses, called momentum crashes. These crashes occur as a result of outperforming past losers relative to winners, in periods when markets rebound after declining in bear markets. Using a comprehensive set of individual stocks in the European stock markets over the period from January 1992 through December 2019, this thesis examines the profitability of the standalone cross-sectional momentum, time series momentum and a dual momentum strategy that combines elements from the two strategies. More importantly, inspired by recent literature, this study proposes a new triple-screened momentum strategy that augments the dual momentum strategy with a market screening step. Cross-comparisons are conducted in order to investigate whether such strategy outperforms its counterparts particularly from the standpoint of avoiding momentum crashes. The findings show that the implemented triple-screened momentum strategy earns significant raw and abnormal risk-adjusted returns and higher Sharpe ratios relative to other momentum strategies and benchmark index. Along with higher mean returns, it appears that this performance is driven by the ability to diminish strings of negative returns associated with momentum crashes. These results are robust across subsamples. Furthermore, this thesis documents the following. First, consistent with prior research, dual momentum outperforms standalone cross-sectional momentum and time series momentum strategies measured by raw and risk-adjusted returns as well as Sharpe ratios. However, the findings indicate that the strategy may be even more prone to momentum crashes compared to the pure momentum strategies. Second, based on the regression tests, the results provide little evidence of abnormal time series momentum effects. In contrast, although the strategy is profitable, the results suggest that time series momentum is largely explained by the cross-sectional momentum premium. According to the results, time series momentum is also subject to momentum crashes. Third, and last, the findings generally corroborate the evidence on cross-sectional momentum. On average, the strategy generates significant raw and abnormal risk-adjusted returns, albeit earns lowest Sharpe ratios relative to its counterparts. In line with prior literature, it is further confirmed that cross-sectional momentum is subject to momentum crashes.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance